Paramedic experiences of providing care in Wales (UK) during the 2020 COVID-19 pandemic (PECC-19): a qualitative study using evolved grounded theory - Nigel Rees; Julia Williams; Lauren Smythe; Chloe Hogan (BMJ Open)
Objective To explore paramedic experiences of providing care during the 2020 COVID-19 pandemic and develop theory in order to inform future policy and practice.Design Qualitative study using constructivist evolved grounded theory (EGT) methodology. One-to-one semistructured interviews were conducted using a general interview guide. Voice over Internet Protocol was used through Skype.Setting Conducted between March 2020 and November 2020 in the Welsh Ambulance Services National Health Services Trust UK which serves a population of three million.Participants Paramedics were recruited through a poster circulated by email and social media. Following purposive sampling, 20 Paramedics were enrolled and interviewed.Results Emergent categories included: Protect me to protect you, Rapid disruption and adaptation, Trust in communication and information and United in hardship. The Basic Social Process was recognised to involve Tragic Choices, conceptualised through an EGT including Tragic personal and professional choices including concerns over personnel protective equipment (PPE), protecting themselves and their families, impact on mental health and difficult clinical decisions, Tragic organisational choices including decision making support, communication, mental health and well-being and Tragic societal choices involving public shows of support, utilisation and resourcing of health services.Conclusions Rich insights were revealed into paramedic care during the COVID-19 pandemic consistent with other research. This care was provided in the context of competing and conflicting decisions and resources, where Tragic Choices have to be made which may challenge life’s pricelessness. Well-being support, clinical decision making, appropriate PPE and healthcare resourcing are all influenced by choices made before and during the pandemic, and will continue as we recover and plan for future pandemics. The impact of COVID-19 may persist, especially if we fail to learn, if not we risk losing more lives in this and future pandemics and threatening the overwhelming collective effort which united society in hardship when responding to the COVID-19 Pandemic.Trial registration number IRAS ID: 282 623.